A Randomised Controlled Comparison of Second‐Level Treatment Approaches for Treatment‐Resistant Adults with Bulimia Nervosa and Binge Eating Disorder: Assessing the Benefits of Virtual Reality Cue Exposure Therapy. (14th August 2017) - Ferrer‐García, Marta; Gutiérrez‐Maldonado, José; Pla‐Sanjuanelo, Joana; Vilalta‐Abella, Ferran; Riva, Giuseppe; Clerici, Massimo; Ribas‐Sabaté, Joan; Andreu‐Gracia, Alexis; Fernandez‐Aranda, Fernando; Forcano, Laura; Riesco, Nadine; Sánchez, Isabel; et al.
Abstract: A question that arises from the literature on therapy is whether second‐level treatment is effective for patients with recurrent binge eating who fail first‐level treatment. It has been shown that subjects who do not stop binge eating after an initial structured cognitive‐behavioural treatment (CBT) programme benefit from additional CBT (A‐CBT) sessions; however, it has been suggested that these resistant patients would benefit even more from cue exposure therapy (CET) targeting features associated with poor response (e.g . urge to binge in response to a cue and anxiety experienced in the presence of binge‐related cues). We assessed the effectiveness of virtual reality‐CET as a second‐level treatment strategy for 64 patients with bulimia nervosa and binge eating disorder who had been treated with limited results after using a structured CBT programme, in comparison with A‐CBT. The significant differences observed between the two groups at post‐treatment in dimensional (behavioural and attitudinal features, anxiety, food craving) and categorical (abstinence rates) outcomes highlighted the superiority of virtual reality‐CET over A‐CBT. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.